How to make money with social media : an insider's guide on using new and emerging media to grow your business - Turner, Jamie , 1961-; Shah, Reshma , 1964- (FT Press, 2011)
This guide is written by experts who've developed money-making marketing campaigns for many of the world's largest companies. This book shows how to avoid crucial pitfalls that other companies have encounter, how to make the most of limited resources, and how to strengthen your brand instead of placing it at risk.--[book jacket]